Comparison of resting masticatory muscle activity among women of different ages - Zieliński, Grzegorz; Byś, Aleksandra; Filipiak, Zuzanna; Baszczowski, Michał; Ginszt, Michał; Suwała, Marta; Szkutnik, Jacek; Majcher, Piotr (Journal of Education, Health and Sport, 2018)
Background: Surface electromyography is one of the test methods allowing to evaluate the bioelectric activity of muscles using the excitability of some tissues. One of the components of the electromyographic study is the recording of resting muscle activity, referred to as passive skeletal muscle tension. The main function of resting tension is to maintain posture with minimal energy costs. The aim of this study was to compare resting masticatory muscle activity between women of different ages. Materials and methods: 75 women were invited to the study, 27 women were admitted after applying the exclusion criteria (average age 22 years ± 2 years). Qualified women were divided into three groups depending on their age: 1st group - 20-year-olds, the 2nd group - twenty-two-year-olds and 3rd group - twenty-four-year-olds. The study involved an 8-channel BioEMG IIITM surface electromyography apparatus with BioPak Measurement System (BioResearch Associates, Inc. Milwaukee, WI, USA). The surface electrodes were distributed bilaterally to the muscle fibre direction of temporal and masseter muscles. The nonparametric U Mann-Whitney test was used for statistical calculations. Statistical significance was determined at 5%. Results: An increase in the resting activity of temporal muscle and a decrease in the resting activity of masseter muscles depending on age were observed. Differences in resting activity were not statistically significant p> 0.05. Conclusions: The results suggest that there are no significant relationships between age and masticatory muscle activity among healthy young women. However, due to the small research group, we recommend further research in this direction.